Third five-year plan and other papers : Papers read at the 12th Pakistan Economic Conference held at Peshawar from March 1 to 3, 1965 - Pakistan Economic Association ([Lahore, 1965)
This consist of papers presented at the 12th Pakistan Economic Conference held at Peshawar from 1 to 3, 1965. Papers presented include: the role of economists in developing economies; evaluation of the second plan; strategy for industrialisation; resource mobilisation; plans and agricultural finance; human resource development; planning for regional development; cost benefits analysis and others.
Bibliographical footnotes.
lje 16/10/18
Loans
Keywords: Economic policy; Economic development; Economic plan; Pakistan